The Concept of Forced Defense As Legal Protection Against the Criminalization of Crime Victims - Suriadiata, Irpan (Faculty of Law, Universitas Pekalongan, 2024)
Article 49 of the Indonesian Criminal Code (KUHP) governs the concept of compelled defense, also known as